Marine litter: One of the major threats for marine mammals. Outcomes from the European Cetacean Society workshop. (April 2019) - Panti, Cristina; Baini, Matteo; Lusher, Amy; Hernandez-Milan, Gema; Bravo Rebolledo, Elisa L.; Unger, Bianca; Syberg, Kristian; Simmonds, Mark P.; Fossi, Maria Cristina
Abstract: Marine litter is a pollution problem affecting thousands of marine species in all the world's seas and oceans. Marine litter, in particular plastic, has negative impacts on marine wildlife primarily due to ingestion and entanglement. Since most marine mammal species negatively interact with marine litter, a first workshop under the framework of the European Cetacean Society Conference, was held in 2017 to bring together the main experts on the topic of marine mammals and marine litter from academic and research institutes, non-governmental organisations, foundations and International Agreements. The workshop was devoted to defining the impact of marine litter on marine mammals by reviewing current knowledge, methodological advances and new data available on this emerging issue. Some case studies were also presented from European waters, such as seals and cetaceans in the North, Baltic, and Mediterranean Seas. Here, we report the main findings of the workshop, including a discussion on the research needs, the main methodological gaps, an overview of new techniques for detecting the effects of marine litter (including microplastics) on marine mammals and, also, the use of citizen science to drive awareness. The final recommendations aim to establish priority research, to define harmonised methods to detect marine litter and microplastics, enforce networking among institutions and support data sharing. The information gathered will enhance awareness and communication between scientists, young people, citizens, other stakeholders and policy makers, and thereby facilitate better implementation of international directives (e.g., the Marine Strategy Framework Directive) in order to answer the question about the actual status of our oceans and finding solutions. Highlights: Harmonised protocols are needed to define the amount of ingested debris that can cause negative effects. Protocols to evaluate the presence and effects of micro and nanoplastics should be further developed. Methods to evaluate the exposure to plastics and plastic additives in free-ranging organisms are required. Communicating to scientists, citizens, stakeholders and policy makers to enhance awareness raising. A consistent monitoring approach is required, as marine litter pollution is estimated to increase. Abstract : To understand the sources, the transfer and the effects of marine litter, and therefore their impacts on marine mammal researchers need to apply a multidisciplinary standardized protocols.